# simplify 3x-5-x+9 and find the value of the expression if x=3​

simplify 3x-5-x+9 and find the value of the expression if x=3​

### 2 thoughts on “simplify 3x-5-x+9 and find the value of the expression if x=3​”

$$\huge{ \red{꧁ℬཞØＫℰη_ℋAℜƬ♡꧂}}$$

$$3x – 5 – x + 9 \\ \rightarrow \: 2x + 4 \: \: \: \: \: \: \: \: \: \: \\ \bold{x = 3} \: \bold{(given)} \\ \rightarrow \: 2 \times 3 + 4 \: \: \: \: \: \\ \rightarrow \: 6 + 4 \: \: \: \: \: \: \: \: \: \: \: \: \\ \rightarrow \: 10 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \:$$

2. ### Given :–

• 3x – 5 – x + 9
• x = 3

### To find :–

• The value of the expression

### Solution :–

Simplification:

$$\implies \bf 3x – 5 – x + 9 \\\\\\ \bf \implies 3x – x + 9 – 5 \\\\\\ \bf \implies 2x + 4 \\\\\\ \dagger \frak { \: Putting \: the \: values \: given \: in \: the \: data} \\ \\ \\ \bf \implies 2(3) + 4 \\\\\\ \implies \bf 6 + 4 \\\\\\ \implies \boxed{\bf 10}$$

Therefore, The value of the expression is 10.

Verification:

$$\bf \implies 3x – 5 – x + 9 \\ \\ \\ \bf \implies 3(3) – 5 – (3) + 9 \\ \\ \\ \bf \implies 9 – 5 – 3 + 9 \\ \\ \\ \bf \implies 4 – 3 + 9 \\ \\ \\ \bf \implies 1 + 9 \\ \\ \\ \implies \boxed{\bf 10}$$

Hence, Verified!

Know more:

$$\boxed{\begin{array} {c|c} \sf{ +,- } & \sf{ – } \\ \dfrac{\qquad\qquad}{} & \dfrac{\qquad}{} \\ \sf{- , +} & \sf{ – } \\ \dfrac{\qquad\qquad}{} & \dfrac{\qquad}{} \\ \sf{+,+} & \sf{ + } \\ \dfrac{\qquad\qquad}{} & \dfrac{\qquad }{} \\ \sf{-,-} & \sf{ + }\end{array}}$$